Comparison of Online and Offline Learning During The COVID-19 Pandemic using Naïve Bayes Method and C4.5 - Aulia, Andini Cahya; Fatekurohman, Mohamat; Tirta, I Made (Universitas Jember, 2023)
Learning is a process of interaction between educators and students who meet the elements of learning carried out in an educational environment, so that learning can develop student’s abilities, interests and talents optimally. In today's era learning is done online and inversely with offline. The purpose of this study is to analyze the comparison of percentages and classification results as well as the results of learning evaluations using the Naïve Bayes method and C4.5. This test is carried out with 4 variables and a comparison of the two methods. The results showed that the accuracy of Naïve Bayes was 74.07% and C4.5. of 77.77% so that the comparison results show that the level of accuracy of the C4.5 method is better than Naïve Bayes. The resulting importance variables are time and effectiveness as well as the results of the classification of learning decisions, namely the offline category as many as 16 data on the Naïve Bayes method and 19 data on the Decision Tree algorithm C4.5 method from 27 input testing data.